Comparison of drug concentrations measured in roadside surveys and in seriously injured drivers in Belgium. Issue 7 (12th November 2012) - Van der Linden, Trudy; Isalberti, Cristina; Silverans, Peter; Legrand, Sara‐Ann; Verstraete, Alain G.
Abstract : The objective of this paper is to compare concentrations of alcohol, illicit, and medicinal drugs in seriously injured drivers and drivers selected randomly at the roadside. Blood samples were analyzed for alcohol, 17 medicinal drugs and 8 illicit psychoactive substances and/or their metabolites by ultra performance liquid chromatography‐tandem mass spectrometry (UPLC‐MS/MS) and gas chromatography mass spectrometry (GC‐MS) in injured drivers admitted to the emergency departments of five hospitals in Belgium between January 2008 and May 2010 and in drivers randomly selected between January 2008 and September 2009. Three hundred and seventy‐seven seriously injured drivers and 2750 roadside respondents were selected. In the roadside survey, out of the 203 concentrations above DRUID (Driving Under the Influence of Drugs, Alcohol and Medicines) cut‐offs for medicinal drugs, 51% were in the therapeutic range, 46% infratherapeutic, and 2.5% supratherapeutic. In the seriously injured drivers, out of the 78 concentrations above DRUID cut‐offs for medicinal drugs, these percentages were respectively 63%, 33%, and 4%. Significant differences were found in the distribution of concentrations for opioids, benzodiazepines, and Z‐drugs. For the latter, while in the seriously injured drivers study most concentrations were therapeutic, in the roadside survey most were infratherapeutic. The opposite was observed for the opioids. Eight and 41% of the roadside respondents and injured drivers, respectively, had an alcohol concentration above 0.1 g/L, with higher concentrations found in the injured drivers. For illicit drugs, significant differences were found for amphetamine and cocaine, for which respectively lower and higher concentrations were observed in the blood samples taken in the roadside survey. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Concentrations of alcohol and illicit and medicinal drugs in seriously injured drivers and drivers selected randomly at the roadside are compared. Significant differences in concentrations between the two populations were observed for some drugs. Alcohol was found in much higher concentrations in the injured drivers.